(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
هدفت الدراسة إلى اختبار فاعلية ثلاثة مبيدات فطرية كيميائية جهازية: بافستين Bavistin (carbendazim 50%WP)، وتاشجارين Tachigarin 30 L (himexazol 30%)، وبلتانول Beltanol SL (chinosol 50%) إضافة إلى المبيد الحيوي بيوكونت- ت Biocont-T WP (Trichoderma harzianum) في مكافحة مرض الذبول الفيوزاريومي على نباتات البندورة المعداة اصطناعياً بالفطر الممرض (Fusarium oxysporum f. sp. lycopersici)، وقدرتها على حماية شتول البندورة من الإصابة بالذبول عند زراعتها بأكياس من البولي إيثيلين في الظروف الطبيعية. نفذت التجارب خلال موسمي 2010 و2011، واستخدمت المبيدات بطريقتين: 1- ري تربة الشتول بمحاليل المبيدات بعد الزراعة مباشرة ، 2- تغطيس جذور الشتول بمحاليل المبيدات قبل الزراعة مباشرة . اعتمدت التراكيز التي تنصح بها الشركات المصنعة في الموسم الأول، وتمت مضاعفة التراكيز في الموسم الثاني . أظهرت النتائج كفاءة جميع المبيدات المستخدمة في تخفيض نسبة الإصابة، وشدتها قياساً بالشاهد عند استخدامها بكلتا الطريقتين. تفوق المبيد الفطري بلتانول على بقية المبيدات المختبرة، وخاصة عند ري التربة بعد الزراعة؛ إذ بلغت نسبة الإصابة 26,66%، وشدتها 22,5%، بعد 40 يوماً في موسم 2011، تلاه المبيد بافستين (30,00%، 26,83%)، دون فروق معنوية بينهما، ثم الحيوي بيوكونت- ت (36,66%،27,5%)، وكان المبيد الفطري تاشجارين (46,66%، 36,66%) أقل المبيدات المختبرة فاعلية في حماية شتول البندورة من الإصابة بالمرض، ولم يلاحظ وجود فروق معنوية بين الطريقتين في قدرة المبيدات على تخفيض نسبة الإصابة بالمرض، وشدتها. The study aimed to evaluate the efficacy of three systemic fungicides: Bavestin WP (carbendazim 50%), Tachigaren 30 L (hymexazol 30%), Beltanol SL (chinosol 50%), and the bio-pesticide Biocont- T WP (Trichoderma harzianum), against tomato wilt disease (Fusarium oxysporum f. sp. lycopersici), under natural conditions. The study was carried out during the 2010 and 2011 seasons. Pesticides were used either by soil irrigation with pesticide solution just after seedling planting, or by dipping the tomato seedlings roots in the pesticide solution just before planting. Pesticides concentrations in the first season were used as suggested by producers, while in the second season the concentration was duplicated. Results showed that all used pesticides were efficient in reducing wilt disease incidence and severity, compared to non- inoculated control. Beltanol proved to be the most effective pesticide when used by soil irrigation in the pesticide solution the percentages of incidence was (26.66%) , and severity was, (22.5%) after 40 days in 2011. followed by Bavestin (30.00%, 26.83%) without significant difference between them and the bio-pesticide Biocont.-T,(36.66%, 27.5%),. whereas Tachigaren (46.66%, 40.00%) was the less effective in protecting from infection. The results also revealed that there was no significant difference between the two contamination methods in terms of ability to reduce disease incidence and severity